How radical is radical realism?. (2nd September 2021) - Cross, Ben
Abstract: Radical realism is distinguished in part from other forms of political realism by its more explicit anti‐status quo objectives. In particular, radical realists generally reject the legitimacy of liberal political institutions, and often defend some version of Marxism or anarchism. However, critics of radical realism sometimes argue that radical realist's aversion to certain kinds of normative theorising hinders their capacity to criticize the status quo. This objection may therefore be best understood as one of "self‐frustration, " rather than "status quo bias." According to the objection, radical realists want to criticise the status quo, but their own methodological positions prevent them from doing so effectively. I have three aims in this article. First, I will clarify the kinds of normativity which radical realists do (and do not) object. Second, I will then show how this enables us to see that the self‐frustration objection fails. Third, I will suggest that it is not radical realism but its critics who may have a problematic relationship with the status quo.